Gambaran Celebrity Worship Terhadap Idola-Kpop pada Mahasiswa Selama Pandemi Covid-19 - Rike Munica (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
This study aims to see how celebrity worship activities are portrayed towards K-pop idols among university students during the Covid-19 pandemic. The description of this research is to look at activities, and what forms of support have been given to K-pop idols that are liked during the pandemic. The research method used is a descriptive research method with a quantitative approach. The data collection technique is in the form of open questionnaires distributed through online media. The subjects in this study totaled 101 participants who were students who liked K-pop idols for at least 3 years with a female gender of 97 and 4 male participants with an age range of 18-23 years. The results showed that the participants were at the entertainment-social level, which is the level of the celebrity worship aspect at the lowest level. Activities carried out during the pandemic were idolizing activities such as live streaming, listening to music, and actively searching for their idols on social media.